Factores asociados al uso de las TIC por docentes en la Institución Pública Inicial N° 258 Greta Raquel Reátegui Vásquez, Nauta 2021 - Lopez Cordova, Rosario (2023)
The purpose of the study was to determine the association of the factors teacher profile, pedagogical innovation and training achieved with the level of use of ICT by teachers in the Initial Public Institution No. 258 Greta Raquel Reátegui Vásquez Nauta 2021. In this sense, the type of relational research together with a bivariate, cross-sectional, and field design. The survey technique and a questionnaire were used to collect data from 40 teachers belonging to the educational institution that made up the population and study sample. 0%) teachers, deficient level, only 5.0% (n=2), regular level, is 35.0% (n=14) and good level is 60.0% (n=24) and the The proposed hypothesis is verified because Kendall's ?-b = 2.779; p-value = 0.000, so the general hypothesis is demonstrated: There is a significant relationship between the factors associated with the level of ICT use in teachers of the I.E.P.I. No. 258 "Greta Raquel Reátegui Vásquez" from Nauta 2021.